Pioneering with UAVs at the battlefield: The influence of organizational design on self-organization and the emergence of safety. (October 2016) - Moorkamp, Matthijs; Wybo, Jean-Luc; Kramer, Eric-Hans
Highlights: A case study was conducted on safety of military UAV operations within Task Force Uruzgan. Emergence of safety was mainly developed by "self-designing" operators. Emergence of safety was hindered by the ad-hoc way Task Force Uruzgan was designed. Findings are used to reflect concepts such as "resilience" and "organizational learning". Abstract: This paper aims to investigate how the ad-hoc and temporary way in which Dutch expeditionary military organizations are designed influenced self-organization and the emergence of safety of UAV operations in Uruzgan. This is done by means of a qualitative case study for which in-depth interviews with operators of the UAV unit within the Task Force Uruzgan were conducted. The analysis shows that developing safe operations depended largely on "self-designing" operators. It is also shown that aspects of Task Force design hindered self-organization and emergence of safety substantially. As a result Task Force design had significant safety consequences for both UAV operations and the operations of Task Force Uruzgan. These findings are used to reflect on contemporary safety management concepts and practices such as "resilience", "percolation" and safety management systems.